Effect of six days of staging on physiologic adjustments and acute mountain sickness during ascent to 4300 meters - Beidleman, B. A.; Fulco, C. S.; Muza, S. R.; Rock, P. B.; Staab, J. E.; Forte, V. A.; Brothers, M. D.; Cymerman, A. (High Altitude Medicine & Biology, 2009)
This study determined the effectiveness of 6 days (d) of staging at 2200m on physiologic adjustments and acute mountain sickness (AMS) during rapid, high-risk ascent to 4300m. Eleven sea-level (SL) resident men (means±SD; 21±3yr; 78±13kg) completed resting measures of end-tidal CO2 (Petco2), arterial oxygen saturation (Sao2), heart rate (HR), and mean arterial pressure (MAP) at SL and within 1h of exposure to 4300m in a hypobaric chamber prior to 6d of staging at 2200m (preSTG) and on the summit of Pikes Peak following 6d of staging at 2200m (postSTG). Immediately following resting ventilation measures, all performed submaximal exercise (55% of altitude-specific maximal oxygen uptake) for 2h on a bicycle ergometer to induce higher levels of AMS. AMS-C, calculated from the Environmental Symptoms Questionnaire, was measured following 4h and 8h of exposure at preSTG and postSTG, and the mean was calculated. Resting Petco2 (mmHg) was unchanged from SL (39.8±2.6) to preSTG (39.3±3.0), but decreased (p<0.05) from preSTG to postSTG (32.8±2.6). Resting Sao2 (%) decreased (p<0.05) from SL (97±2) to preSTG (80±4) and increased (p<0.05) from preSTG to postSTG (83±3). Resting HR (bpm) and MAP (mmHg) did not change in any of the test conditions. The incidence and severity of AMS-C decreased (p<0.05) from preSTG (91±30%; 1.05±0.56) to postSTG (45±53%; 0.59±0.43), respectively. These results suggest that modest physiologic adjustments induced by staging for 6d at 2200m reduced the incidence and severity of AMS during rapid, high-risk ascent to 4300m.